Causes and Consequences of Deindustrialization in the Euro Area - Mucha-Leszko, Bogumiła (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2016)
The post-industrial stage of development reached in developed countries is characterized by an increase in services' share and the progressive decline of the manufacturing share in their economies. The intensification of deindustrialization process heated up the discussion pertaining to its impact on the weakening of investment, technological progress, innovation, and a decline in labour productivity and GDP growth. The aim of the paper is to present the scale and consequences of deindustrialization in the euro area based on analysis of manufacturing and other sectors shares in the gross value added and employment in the euro area. The indicators used for the assessment of deindustrialization consequences are: labour productivity and total factor productivity (TFP) growth rates. As the outcome of conducted analysis, the author has drawn two main conclusions: 1) the decreasing importance of manufacturing limits the possibility of carrying out research projects and creating technological progress, 2) the negative TFP growth rate, declining of labour productivity growth rate in 2008-2015 and the decrease of GDP testifies to the threat of secular stagnation in the euro area.